Factors influencing food waste in restaurants and their impact on processing: An interpretative structural modelling approach - Cahyana Atikha Sidhi; Ainiyah Sakina; Nurmalasari Intan Rohma; Saidi Ida Agustini (BIO Web of Conferences)
Food waste is a significant issue in Indonesia, with approximately 1.3 billion tonnes generated annually. A substantial portion of this waste originates from restaurants, often due to customers not finishing their meals. The contribution of this research is to provide proposals for handling food waste. This study employs Interpretative Structural Modelling (ISM) to identify and analyse factors influencing food waste in restaurants. The study identifies 23 factors affecting food waste in restaurants, which are classified using the SCOR method. ISM analysis reveals a hierarchical structure of these factors based on expert opinions. Food packaging is identified as a critical factor contributing to food waste due to its potential to damage food. Addressing packaging issues should be prioritized to reduce food waste, whereas factors related to food delivery have a relatively lower impact.